Action of Arrabidaea chica extract on Candida albicans biofilms, cytotoxic effect on fibroblasts and keratinocytes, and on physical/mechanical porperties of poli(methylmethacrylate) resin (Research, Society and Development, 2021)
This study investigated the action of the hydroalcohol extract Arrabidaea chica (AchE) against C. albicans, as well as its effect on cytotoxicity in fibroblasts and keratinocytes and changes in the physical/mechanical properties of PPMA resin. The susceptibility of C. albicans to AchE was assessed using the MIC and MFC. For the susceptibility test, C. albicans biofilms were developed in PMMA acrylic resin disc for 48 hours and immersed in 5 groups, phosphate-saline buffer, NaoCl 1% or in AchE at CIM, 5xCIM or 10xCIM. The cytotoxicity of AchE (10, 50 and 100 µg /mL) in fibroblasts and keratinocytes was evaluated by MTT, with distilled water and NaOCl l% used as controls. For evaluation of physical/mechanical properties, discs were immersed in the 5 already described groups. The discs were incubated and the testes were performed after 0, 7, 14, 21 and 28 days of immersion. Surface roughness, color change and flexural strength were verified. AchE was considered a strong inhibitor and with bactericidal potential. At 10 µg/mL it did not show cytotoxicity compared to the control group. Other experimental groups were cytotoxic, however, with lower values when compared to NaOCl 1%. There were no significant differences in group-independent physical/mechanical properties or time taken. AchE, when used in high concentrations, was cytotoxic and, regardless of the tools used, it did not interfere with the physical/mechanical properties of PMMA resins.